Sense of agency predicts severity of moral judgments - Spaccasassi, Chiara; Cenka, Kamela; Petkovic, Stella; Avenanti, Alessio (Frontiers in Psychology, 2023)
Sense of Agency (SoA) refers to the awareness of being the agent of our own actions. A key feature of SoA relies on the perceived temporal compression between our own actions and their sensory consequences, a phenomenon known as ‘Intentional Binding’. Prior studies have linked SoA to the sense of responsibility of our own action. However, it is unclear whether SoA predicts the way we judge the actions of others – including the judgment of morally wrong actions like harming others. To address this issue, we ran an on-line pilot experiment where participants underwent two different tasks designed to tap into SoA and moral cognition. SoA was measured using the Intentional Binding task which allows to obtain an implicit (Intentional Binding) and explicit (Agency Rating) measure of SoA. Moral cognition was, instead, assessed by asking the same participants to evaluate videoclips where an agent could deliberately or inadvertently provoke suffering to a victim (Intentional vs Accidental Harm) and Neutral scenarios. Results showed a significant relationship between both implicit and explicit measures of SoA and the moral evaluation of the Accidental Harm scenarios, with stronger SoA predicting stricter moral judgments. These findings suggest that our capability to feel in control of our actions predicts the way we judge others’ actions, with stronger feeling of responsibility of our own actions predicting the severity of moral evaluations of other actions, particularly in ambiguous scenarios characterized by an incongruency between an apparent innocent intention and a negative action outcome.